(untitled) (Tempo e Argumento, 2016)
The aim of this paper is analyzing some of the scenarios, photos, and posters used by the Peronist administration and explain their incidence in wine festivals and their imaginary construction after World War II. This proposal examines the relation between photography and ephemeral architecture mediated by political power, as a part of the strategies developed by the Peronist propaganda apparatus to feed the imaginary surrounding the ‘New Argentina.’ At this particular historical moment, the graphic and photographic records taken into account are a gateway to analyze the ephemeral phenomena that cannot be resumed otherwise. The methodological strategy used is qualitative and exploratory, and its design has a flexible nature. Although these testimonies, reflected in the sources described, do not give us back the possibility of being in direct contact to these experiences, they do allow us to access the set of desires, tensions, frustrations, expectations, debates, the achievements and failures, through which the scenic architecture projects were formulated and developed. Keywords: Photographic Archives; Ephemeral Architecture; Harvest Festival; Power Relationships; Peronism. Original title: La fiesta peronista: recorridos y apropiaciones entre fotografía, arquitectura efímera y poder político.